179k views
13 votes
Fundamental theorem of calculus

g(s)=\int\limits^s_6 {(t-t^4)^6} \, dt

1 Answer

3 votes

Answer:


\displaystyle g'(s) = (s-s^4)^6

Explanation:

The Fundamental Theorem of Calculus states that:

\displaystyle (d)/(dx)\left[ \int_a^x f(t)\, dt \right] = f(x)

Where a is some constant.

We can let:

\displaystyle g(t) = (t-t^4)^6

By substitution:


\displaystyle g(s) = \int_6^s g(t)\, dt

Taking the derivative of both sides results in:

\displaystyle g'(s) = (d)/(ds)\left[ \int_6^s g(t)\, dt\right]

Hence, by the Fundamental Theorem:


\displaystyle \begin{aligned} g'(s) & = g(s) \\ \\ & = (s-s^4)^6\end{aligned}

User MachineElf
by
5.9k points